Volatilização de amônia com o uso de dejetos de suínos com pH modificado - Muller, Fernando (2018)
In western Paraná the production of pigs in feedlot system is in a large scale, resulting in a wide production of manure with a high power of environmental pollution if not treated correctly. The use of this manure as biofertilizers may be an interesting alternative for the agricultural sector by providing nutrients to plants, especially nitrogen. In addition, the biofertilizer can improve soil fertility by increasing its organic matter. However, after the application of nitrogen to the soil, gaseous losses of this nutrient may occur, denominated ammonia volatilization, which can be intensified by different factors. Thus, the objective of this work was to evaluate the fertilization of soybean with liquid swine manure and the loss of nitrogen by volatilization after the application of it with different pHs. The work was conducted in two experiments. The first one was conducted in the 2015/2016 under no-tillage system with soybean crop. On the day of sowing, the treatments were composed of three doses of liquid swine manure (48; 96 and 144 m3 ha-1), plus additional treatments, which were the control (without fertilization) and a treatment with mineral fertilization (300 kg ha-1 of NPK formulation 04-30-10). The productivity of grains, green stems, heights of plants and one hundred grain mass were analyzed. The second work was conducted in a greenhouse during the period from October to December 2017. The ammonia volatilization was evaluated according to the adjusted pH of the liquid swine manure, being 3.0; 4.0; 5.0; 6.0 and 7.4 (natural manure). Further, two additional treatments were evaluated: natural manure + agricultural gypsum and the control (without application of manure). In order to capture the volatilized ammonia, Sale type collectors were used, with a static free semi-open chamber. The volatilization flow, accumulated volatilization and percentage of ammonia loss were analyzed. The mineral fertilization of soybean crop can be replaced by fertilization with liquid swine manure, mainly in high fertility soils. The fertilization with 48 m³ ha-1 was able to supply the nutritional need of the soybean crop according to the productivity obtained. The application of liquid swine manure with natural pH (7,4) provided high losses of ammonia, around 46 % higher. With the acidification of the manure by adjusting the pH around 3 to 5, a great reduction to 5 % of loss of nitrogen by volatilization was observed.